Strategi Peningkatan Pemasaran Produk Kredit di Perumda BPR Bank Magelang - Prasetyo, Radita; Rahardjo, Budi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Perumda BPR Bank Magelang has various credit products in Magelang, Perumda BPR Bank Magelang has played a role in financing credit to the Magelang community, but competitive competition requires Perumda BPR Bank Magelang to implement marketing strategies that are in accordance with the current situation and conditions. The purpose of this study is to analyze marketing strategies using SWOT analysis on Perumda BPR Bank, the results of the analysis of Perumda BPR Bank are Perumda BPR Bank Magelang is in quadrant 1 or aggressive and is in a very profitable position, and the strategy that has the greatest value is the SO strategy. Therefore, the strategies that can be applied by Perumda BPR Bank Magelang are increasing marketing strategies to add new market share, establishing good cooperation with stakeholders, improving services to retain and attract customers.